2021
DOI: 10.3389/fcvm.2021.629268
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Big Endothelin-1 at Admission Is Associated With Poor Short-Term Outcomes in Patients With Acute Decompensated Heart Failure

Abstract: Objective: We aimed to evaluate the association between plasma big endothelin-1 (ET-1) at admission and short-term outcomes in acute decompensated heart failure (ADHF) patients.Methods: In this single-center, retrospective study, a total of 746 ADHF patients were enrolled and divided into three groups according to baseline plasma big ET-1 levels: tertile 1 (<0.43 pmol/L, n = 250), tertile 2 (between 0.43 and 0.97 pmol/L, n = 252), and tertile 3 (>0.97 pmol/L, n = 244). The primary outcomes were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Heart failure, atrial fibrillation, and ischemia/reperfusion injury are typical lesions of endocardial endothelium. These kinds of patients may have systemic endothelial dysfunction, which combines the dysfunction of endocardium and vascular endothelium and leads to the increase of hemodynamic load of the left atrium and the increase of synthesis and release of ET-1 and angiotensin II [ 18 , 19 ]. In this study, the expression level of serum ET-1 in sepsis patients complicated with heart failure was significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure, atrial fibrillation, and ischemia/reperfusion injury are typical lesions of endocardial endothelium. These kinds of patients may have systemic endothelial dysfunction, which combines the dysfunction of endocardium and vascular endothelium and leads to the increase of hemodynamic load of the left atrium and the increase of synthesis and release of ET-1 and angiotensin II [ 18 , 19 ]. In this study, the expression level of serum ET-1 in sepsis patients complicated with heart failure was significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the concentrations of ET-1, which were significantly higher in patients with HTN, the concentrations of the precursor Big ET-1 did not differ significantly from those of controls ( Figure 2 ). Probably, elevated levels of Big ET-1 in patients with HTN can be detected when there is either concomitant heart failure [ 34 , 35 ], pulmonary HTN [ 36 , 37 ], coronary artery disease [ 38 , 39 ], or in combination. Interestingly, Big ET-1 and ET-1 levels were high in patients with arsenic (As)-induced HTN, which is thought to be mediated by oxidative stress as a result of chronic As exposure [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other cardiovascular conditions, ET-1 levels are elevated in the blood samples of chronic HF patients of various etiologies, including diabetic cardiomyopathy and hypertrophic cardiomyopathy [200,201]. One study related natriuresis, fluid congestion, and poor clinical prognosis to the elevation of plasma ET-1 levels, while another indicated that a higher ET-1 plasma level at admission is a prognostic marker for poor short-term prognosis in acute heart failure (HF) [202,203]. Chronic HF due to ischemic heart disease has also been correlated clinically with ET-1.…”
Section: Clinical Evidence Of Endothelin In Chronic and Acute Heart F...mentioning
confidence: 99%